Prevalence of type 2 diabetes mellitus and impaired glucose tolerance in Asian women with polycystic ovary syndrome - S. Weerakiet (2018)
Objectives: To determine the prevalence of abnormalities of glucose metabolism in Asian women with polycystic ovary syndrome (PCOS) and to assess the different impacts of the 1985 and 1999 WHO consultations and the ADA criteria for the diagnosis of type 2 diabetes mellitus (DM). Methods: Eighty-five women with PCOS were consecutively included in the study at the Reproductive Endocrinology Unit, Department of Ob-Gyn, Ramathibodi Hospital, Mahidol University. All women underwent a standard oral glucose tolerance test (OGTT). Fasting insulin and testosterone levels were also measured. Results: Seventy-nine women consented to the OGTT. The prevalence of impaired glucose tolerance (IGT) and type 2 DM was 22.8 and 15.2% with the 1985 WHO criteria, and 20.3 and 17.7% according to the 1999 WHO consultation criteria, respectively. The recommendation of the ADA using the fasting glucose levels could only determine a prevalence of 6.3% for type 2 DM. The fasting insulin and testosterone levels were significantly higher in DM than IGT and normal glucose tolerance (NGT) subgroups. The PCOS women with abnormalities of glucose metabolism had a greater body mass index (BMI), higher fasting glucose and 2-h post-load glucose levels than those with NGT. The prevalence of glucose intolerance significantly increased with BMI. Conclusions: Similar to other ethnic populations, Asian women with PCOS are at risk of developing IGT and type 2 DM especially if obese. The recommendation of the ADA is not appropriate for the diagnosis of type 2 DM in PCOS women. © 2001 International Federation of Gynecology and Obstetrics. All rights reserved.